Low Lifetime Risk of Contralateral Breast Cancer in a Middle-Income Asian Country: Evidence to Guide Post-treatment Surveillance - See, Mee Hoong; Bhoo-Pathy, Nirmala; Jamaris, Suniza; Kiran, A.; Evans, Dafydd Gareth; Yip, Cheng Har; Mohd Taib, Nur Aishah (Springer Verlag (Germany), 2018)
Background: The rate of contralateral risk-reducing mastectomy (CRRM) is increasing in the West with controversial evidence of improved survival in early breast cancer patients. Although uptake of CRRM in Asia appears low, the trends may rise, and there is currently an urgent need to provide evidence for informed decision-making in clinical practice. This study aims to determine the risk of contralateral breast cancer (CBC) and its associated factors in an Asian setting. Method: A total of 2937 newly diagnosed patients with stage I and stage II breast cancer in University Malaya Medical Centre between Jan 1993 to Dec 2012 were included in the study. Multinomial logistic regression analysis allowing death to compete with CBC as a study outcome was used; patients with unilateral breast cancer who were alive were taken as reference. A stepwise backward regression analysis including age at diagnosis, ethnicity, family history of breast cancer, TNM stage, hormonal receptor status, HER2 status, chemotherapy, radiotherapy, and hormone therapy was conducted. Results: Fifty women developed CBC, over a median follow-up of 6 years. The 5- and 10-year cumulative risk of contralateral breast cancer was 1.0% (95% CI 0.6–1.4%) and 2.8% (95% CI 2.0–3.6%), respectively. Young age at diagnosis of first cancer, positive family history, and stage I disease were independent predictors of CBC. Discussion: The current study suggests that the risk of CBC is very low in a Southeast Asian setting. Any recommendations or practice of CRRM should be reviewed with caution and patients must be counseled appropriately.